Enhancing second language learners' persuasive presentation skills using video analyses - Lilisuriani binti Abdul Latif @ Bapoo (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
Communicating persuasively is a skill that is needed in both academic and business contexts and yet, second language learners have often been reported to be lacking the skill to persuade. Thus, there is a need to equip the learners with persuasive communication skills. To determine a way to enhance second language learners' persuasive presentation skills, a sequential mixed-methods research was conducted with the purpose of investigating the extent to which video analyses enhance second language learners' abilities to present persuasively. Pre- and post-tests quasi-experiment was carried out involving 43 second language learners of English from a public university in Malaysia. In the pre-test, a group of thirty learners were asked to present persuasively and their presentations were video-taped. The learners were then asked to analyse their presentations in the videos. This was in contrast to another group of learners who also presented, was video-taped but did not do any video analyses. Both groups presented again in the post-test where they were evaluated by a group of professional audience. The language used by second language learners who did the video analyses was examined and compared to the learners who did not carry out any analysis. Frequency counts of the metadiscourse markers used by the learners in both groups in their presentations were compared. Ratings given by the professional audience to both groups of learners were also compared. The second language learners who analysed their presentations in the videos were then interviewed on the impacts of the activity on their persuasive presentation skills. The findings indicate higher mean scores for the metadiscourse markers used to create persuasive appeals among the learners who adopted the video analyses. They also had higher mean scores for the ratings given by the audience. In the interviews, the second language learners also revealed that the video analyses were helpful in preparing them for their presentations. This research asserts that video analyses are useful in enhancing the abilities of second language learners of English to present persuasively.